A Petri-Net Based Representation of Automated Railway Signalling System with Collision Avoidance - Barik, R; Santara, K; Ghosh, R; Sarkar, P (International Journal of Computer Sciences and Engineering, 2025)
In today’s fast going life railway plays a major role as a public transport in different countries. And it’s a very difficult job to control the railway traffic signal manually considering all kinds of situation and also it is very difficult to find out whether any deadlock situation has occurred or not. This work is emphasized on use of Petri nets in modeling railway network as well as railway signalling system and designing appropriate control logic for it to avoid collision. Here, the whole railway network is presented as a combination of the elementary models – tracks, stations and points (switch) within the station including sensors and semaphores. We use generalized mutual exclusion constraints and constraints containing the firing vector to ensure safeness of the railway network. In this research work, we have actually introduced constraints at the points within the station. These constraints ensure that when a track is occupied, we control the switch so that another train will not enter into the same track and thus avoid collision.